Zero sugar diet : the 14-day plan to flatten your belly, crush cravings, and help keep you lean for life - Zinczenko, David; Perrine, Stephen (Ballantine Books, 2016)
"Lose up to a pound a day and curb your craving for sweets with delicious recipes and simple, science-based food swaps from David Zinczenko, Good Morning America's health and wellness editor and bestselling author of Zero Belly Diet, Zero Belly Smoothies, and Eat This, Not That!"--Amazon.com.